The Influence of TikTok on Elementary Students’ Interpersonal Communication in Learning Contexts - Fahira, Mutya; Saputra, Ayub Qadhafi; Fatimah, Nunung (FKIP - Universitas Riau, 2025)
The growing popularity of TikTok among elementary school students has raised questions about its potential impact on how students communicate, especially within learning environments. This study aims to examine whether the use of the TikTok social media platform affects the interpersonal communication styles of fifth-grade students at SDN 62 Rontu. A quantitative research approach was used with a survey method. Data were collected from 19 students using a questionnaire that was validated by an expert in elementary education. The Kolmogorov-Smirnov normality test showed that the data were normally distributed (sig. = 0.200), and Levene’s test confirmed the homogeneity of variance (sig. = 0.063). The result of the t-test indicated a significance value greater than 0.05, which means there was no significant influence of TikTok usage on students’ communication styles. Although students were fairly active on TikTok and followed various communication trends from the platform, these habits did not directly shape the way they communicated in daily learning contexts. The findings suggest that communication behaviors are more strongly influenced by family interaction, peer relationships, and school culture rather than social media use.